A ANALYSIS OF FACTORS INFLUENCING THE LONGITUDE 1ST STAGE AT SUMBER GLAGAH HOSPITAL, MOJOKERTO - Yulianti, Indra; Yanti, Ariu Dewi; Prihartini, Sabrina Dwi (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Childbirth is a physiological thing, but in some cases of childbirth there are still factors that complicate things and cause complications during the birth process. The duration of the first stage of labor in parturient mothers is influenced by maternal, fetal and helper factors. The occurrence of problems with one of these factors can cause difficulties during labor, thereby impacting the length of labor. This is very important and needs to be taken into account considering that several cases of maternal and infant deaths are due to not being detected early. The aim of this research is to analyze factors that influence the length of the first stage of labor. This research is analytical research by processing secondary data using a case control approach. The population in this study was all mothers giving birth in January-December 2022 at the Sumber Glagah Regional Hospital, Mojokerto, totaling 130 people. The sampling technique uses total sampling. The statistical test used is the Spearman Rank test. The results of the study showed that there was a relationship between the mother giving birth and the mother's age with a value of p: 0.005 (OR=41), there was a relationship between pregnancy spacing and the first stage lengthened p: 0.004 (OR=10), there was a relationship between parity and the first stage lengthened p : 0.004 (OR=6), there is a relationship between the baby's weight and the first stage of prolongation p : 0.005 (OR=45). From the research results, it is hoped that health workers can pay attention to risk factors in pregnancy that influence the birthing process. Application of maternal care to speed up the birthing process